Accessing clinical services and retention in care following screening for hypertension and diabetes among Malawian adults: an urban/rural comparison. Issue 11 (November 2016) - Musicha, Crispin; Crampin, Amelia C.; Kayuni, Ndoliwe; Koole, Olivier; Amberbir, Alemayehu; Mwagomba, Beatrice; Jaffar, Shabbar; Nyirenda, Moffat J.
Abstract : Objective: Interventions to impact on the burden of chronic noncommunicable diseases, such as hypertension and diabetes, include screening of asymptomatic adults, but little is known about the subsequent course of clinical care. We report on the uptake of referral for clinical assessment and retention in care, following a large urban/rural population screening program in Malawi. Methods: Adult residents were screened for raised blood pressure and raised fasting blood glucose at a demographic surveillance site in rural Karonga District and in urban Area 25, Lilongwe with well supported chronic care clinics. Successful uptake was defined as presenting for clinical assessment within 6 weeks of referral, and nonattenders were followed at home. Logistic regression was used to examine association of uptake with demographic and clinical factors. Retention was assessed using survival analysis techniques. Results: A total of 27 305 participants were screened for hypertension and diabetes between May 2013 and September 2015. Of these, 4075 (14.9%) were referred for suspected hypertension (3640), diabetes (172), or both (263). Among those referred, 2480 (60.9%), reported for clinical assessment. Factors associated with uptake of care included being female, rural residency, older age, unemployment, prior medication, and diabetes. Retention, for those enrolled in care following a formal clinical assessment, was associated with the final diagnosis following clinical assessment, rural residency, and older age. Conclusion: Screening for hypertension and diabetes identifies large numbers of individuals who need further clinical assessment, but strategies are needed to ensure better linkage and retention into care.